E-waste CRT panel glass reinforced magnesium composite processed through powder metallurgy: fabrication and mechanical performance evaluation - Gopal, P.M.; Prakash, K. Soorya; Makki, Emad; Kavimani, V.; Giri, Jayant; Sathish, T. (Journal of materials research and technology, 2023)
Cathode Ray Tube (CRT) panel glass with higher silica content has a potential to be used as reinforcement material in magnesium matrix composites. The present study aims to formulate a wear resistant magnesium hybrid composite by reinforcing silica rich E-waste CRT panel glass powder (0, 10 and 20 wt. %) and boron nitride (0, 2 and 4 wt. %) solid lubricant processed through powder metallurgy route. Composition of the CRT panel glass powder is identified through EDS and XRD analysis is performed for both base material and reinforcements. The developed green MMC shows increased hardness (∼53 %), porosity (∼7 %) and density (∼7 %) with respect to addition of CRT reinforcement. Porosity of hybrid composite increased vastly to 9.2 % when the CRT and BN content are increased to 20 % and 4 % respectively. A slight increment in (10 %) hardness is observed for 2 % addition of BN with Mg and Mg/CRT composite whereas hardness of the Mg and Mg/CRT MMC decreases with further addition of BN. The wear resistance of the composite enhanced with raise in CRT and BN content whereas the co efficient of friction decreases with increases in BN percentage. Corrosion behaviour of Mg is also analysed and found enhanced with reinforcement addition. It is identified from the results that the addition of CRT% up to 10 % yields significant results whereas further increase in CRT % to 20 provides only minor enhancements in properties. Further, it is suggested to restrict the addition of BN to 2 %.